ATP-dependent regulation of sodium-calcium exchange in Chinese hamster ovary cells transfected with the bovine cardiac sodium-calcium exchanger - Condrescu,M.; Gardner,J.P.; Chernaya,G.; Aceto,J.F.; Kroupis, C.; Reeves,J.P. (J.Biol.Chem., 1995)
Chinese hamster ovary cells expressing the bovine cardiac Na/Ca exchanger were treated with ouabain to increase [Na+]i and stimulate Ca2+ influx by Na/Ca exchange. Depletion of cellular ATP inhibited 45Ca uptake by 40% or more and reduced the half-maximal Na+ concentration for inhibition of 45Ca uptake from 90 to 55 mM. ATP depletion also reduced the rate of rise in [Ca2+]i when [Na+]o was reduced and inhibited the decline in [Ca2+]i when high [Na+]o was restored. The effects of ATP depletion were either absent or reduced in cells expressing a mutant exchanger missing most of the cytosolic hydrophilic domain. We were unable to detect a phosphorylated form of the exchanger in immunoprecipitates from 32P-labeled cells. ATP depletion caused a breakdown in the actin cytoskeleton of the cells. Treatment of the cells with cytochalasin D mimicked the effects of ATP depletion on the [Na+] inhibition profile for 45Ca uptake. Thus, ATP depletion inhibits both the Ca2+ influx and Ca2+ efflux modes of Na/Ca exchange, and may alter the competitive interactions of extracellular Na+ and Ca2+ with the transporter. The latter effect appears to be related to changes in the actin cytoskeleton
DA - 19950523 IS - 0021-9258 (Print) IS - 0021-9258 (Linking) LA - eng PT - Journal Article PT - Research Support, U.S. Gov't, P.H.S RN - 0 (Actins) RN - 0 (Carrier Proteins) RN - 0 (Sodium-Calcium Exchanger) RN - 22144-77-0 (Cytochalasin D) RN - 8L70Q75FXE (Adenosine Triphosphate) RN - 9NEZ333N27 (Sodium) RN - SY7Q814VUP (Calcium) SB - IM
Keywords: Actins; Adenosine Triphosphate; Animals; calcium; Carrier Proteins; Cattle; Cho Cells; Cricetinae; Cytochalasin D; Hydrogen-Ion Concentration; metabolism; Myocardium; pharmacology; physiology; sodium; Sodium-Calcium Exchanger; Transfection